Medical accessibility and underreporting of occupational diseases: effect of travel distance and travel time - Chen, Ping Hui; Chu, Po-Ching; Huang, Ching-Chun; Chen, Chi-Hsien; Guo, Yue Leon; Su, Ta-Chen; Chen, Pau-Chung (Frontiers in Rehabilitation Sciences, 2025)
ObjectivesUnderreporting of occupational diseases (ODs) could be attributed to poor medical accessibility, which is rarely discussed previously. Our cross-sectional study aims to evaluate how OD reporting is impeded by long travel distance/time (TD/TT) to the nearest major occupational medicine clinics.MethodsUsing data from the Network of Occupational Diseases and Injuries Service (NODIS), Taiwan's OD surveillance system, and the annual Manpower Survey from 2008 to 2018, we calculate each district's incidence rate of ODs (IROD) and expected IROD based on industries and job titles. Each town's TD/TT to the nearest major occupational medicine clinics is estimated by Google Maps’ Distance Matrix API. The quasi-Poisson regression model is used to investigate the effect of TD and TT on IROD, while industries and job titles are adjusted by offsetting expected IROD. A subgroup analysis is then carried out to check the effect of employment status, sickness absence, and reporting years.ResultsA total of 3,420 cases of definite ODs are included in our study. Using the quasi-Poisson regression model, after adjusting industry types and job titles, TD and TT have a significant effect on IROD. As TD/TT increases by 10 km/10 min, IROD decreases by 10.90%/10.73%. It is estimated that ∼200 OD cases per year or 40% of ODs are therefore underreported. In the subgroup analysis, only mildly sick workers are still significantly affected by TD and TT.ConclusionsOur study shows how poor medical accessibility leads to underreporting, especially for mildly sick cases, and up to 40% of ODs could be underreported. Using this method, we can evaluate the cost-effectiveness of adding reporting hospitals in areas with poor medical accessibility.